Predictors of family functionality amongst human immunodeficiency virus-serodiscordant couples in two major hospitals in Kumasi, Ghana - Nana K. Ayisi-Boateng; Anthony Enimil; Aliyu Mohammed; Akye Essuman; Henry Lawson; Douglas Opoku Aninng; David Agyemang-Yeboah; Kathryn Spangenberg (AOSIS, 2020)
Background: Family instability and partner conflicts are reportedly common in serodiscordant relationships. To date, the family adaptability, partnership, growth, affection and resolve (Family APGAR), a standardised tool for assessing family function, has not been used in any published literature involving this peculiar group. Aim: The aim of this study was to determine the predictors of family functionality and its association with human immunodeficiency virus (HIV) serodiscordance. Setting: The study was undertaken at the Kwame Nkrumah University of Science and Technology Hospital and Komfo Anokye Teaching Hospital in Kumasi, Ghana. Method: This was a cross-sectional study. A systematic sampling method was used to select HIV-positive clients whose partners were seropositive (concordant) or seronegative (discordant). A standardised format was used to extract relevant data. All data were analysed using STATA® (version 14). Results were reported as odds ratios with 95% confidence intervals for study and outcome variables. Results: The study recruited 374 respondents, of which 52% (195) were in HIV-discordant relationships. Approximately 68% (254) of the respondents rated their families as functional, 15% (57) rated as moderately dysfunctional and 17% (63) rated as severely dysfunctional. A statistically significant relationship was found between family functionality and gender, as well as between family functionality and HIV status disclosure to the partner. No association was found between the Family APGAR and HIV serodiscordance. Conclusion: Amongst HIV couples, the strongest predictors of family functionality are gender and status disclosure. Healthcare providers should invest efforts into addressing gender-based challenges, utilise the Family APGAR and support disclosure of HIV status, especially amongst discordant couples.